Community-based benchmarking improves spike rate inference from two-photon calcium imaging data. - Philipp Berens; Jeremy Freeman; Thomas Deneux; Nikolay Chenkov; Thomas McColgan; Artur Speiser; Jakob H Macke; Srinivas C Turaga; Patrick Mineault; Peter Rupprecht; Stephan Gerhard; Rainer W Friedrich; et al. (PLoS Computational Biology, 2018)
In recent years, two-photon calcium imaging has become a standard tool to probe the function of neural circuits and to study computations in neuronal populations. However, the acquired signal is only an indirect measurement of neural activity due to the comparatively slow dynamics of fluorescent calcium indicators. Different algorithms for estimating spike rates from noisy calcium measurements have been proposed in the past, but it is an open question how far performance can be improved. Here, we report the results of the spikefinder challenge, launched to catalyze the development of new spike rate inference algorithms through crowd-sourcing. We present ten of the submitted algorithms which show improved performance compared to previously evaluated methods. Interestingly, the top-performing algorithms are based on a wide range of principles from deep neural networks to generative models, yet provide highly correlated estimates of the neural activity. The competition shows that benchmark challenges can drive algorithmic developments in neuroscience.